Compound odontoma - Monica Yadav; Pournima Godge; S M Meghana; Sandip R Kulkarni (Wolters Kluwer Medknow Publications, 2012)
Odontomas have been extensively reported in the dental literature, and the term refers to tumors of odontogenic origin. Though the exact etiology is still unknown, the postulated causes include: local trauma, infection, inheritance and genetic mutation. The majority of the lesions are asymptomatic; however, may be accompanied with pain and swelling as secondary complaints in some cases. Here, we report a case of a compound odontome in a 14 year old patient.